2014
DOI: 10.1039/c3ob41800f
|View full text |Cite
|
Sign up to set email alerts
|

An advanced and novel one-pot synthetic method for diverse benzo[c]chromen-6-ones by transition-metal free mild base-promoted domino reactions of substituted 2-hydroxychalcones with β-ketoesters and its application to polysubstituted terphenyls

Abstract: Novel and efficient one-pot syntheses of a variety of benzo[c]chromen-6-one derivatives were accomplished using Cs2CO3-promoted reactions between substituted 2-hydroxychalcones and β-ketoesters. These reactions involved domino Michael addition/intramolecular aldol/oxidative aromatization/lactonization and provided a rapid synthetic route for the production of biologically interesting novel benzo[c]chromen-6-one molecules bearing several different substituents on benzene rings. As an application of this methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…Although the crude NMR spectrum indicated that 2,4-dihydroxybenzylideneindenedione managed to yield the desired coumarin 5k, the compound was tedious to purify. Based on our findings and the literature, 30…”
Section: Scheme 2 Synthesis Of 2-hydroxybenzylideneindenediones 3a-kmentioning
confidence: 56%
See 1 more Smart Citation
“…Although the crude NMR spectrum indicated that 2,4-dihydroxybenzylideneindenedione managed to yield the desired coumarin 5k, the compound was tedious to purify. Based on our findings and the literature, 30…”
Section: Scheme 2 Synthesis Of 2-hydroxybenzylideneindenediones 3a-kmentioning
confidence: 56%
“…28 The base-mediated reactions of diethyl 1,3-acetonedicarboxylate with 2-hydroxychalcones have been employed in the synthesis of benzene fused coumarins (Scheme 1). [29][30][31] O OMe However, the reaction of substituted -keto esters with 2-(2-hydroxybenzylidene) of both cyclic and acyclic 1,3-dicarbonyl compounds have never been studied. This type of reactions could provide a template for the synthesis of a wide variety of new fused coumarins.…”
Section: Figure 1 Fluorenone and Natural Products Containing Fluorenonementioning
confidence: 99%
“…From a Cambridge Structural Database search (Groom et al, 2016), we found compounds identified by refcodes OKEYUB (Xiao et al, 2021), QABVEY (Wang et al, 2021), ALTENU (McPhail et al, 1973), AMUYIS (Alzaydi et al, 2016), ANOVEG (Sosnovskikh et al, 2016), ANOVIK (Sosnovskikh et al, 2016), BUWJEK (Parveen et al, 2015), BUXLOW (Fatunsin et al, 2010), DIPTUR (Casiraghi et al, 1986), DISJAS (Lee et al, 2013), SEDFEN (Appel et al, 2006), SIVQIZ (Poudel & Lee, 2014), SIJZER (Hussain et al, 2007), TUPJOE (Siegel et al, 2010), ZAQHIK (Dasari et al, 2012) and IZACIY (Duan et al, 2021) to be similar to the title compound.…”
Section: Structure Descriptionmentioning
confidence: 99%
“…Similarly, we investigated a new and efficient method for the synthesis of biologically interesting benzo[ c ]chromen‐6‐one derivatives 26 from readily available substituted 2‐hydroxychalcones 24 and β‐ketoesters 25 through tandem Michael addition/intramolecular aldol/aromatization/lactonization reactions by using two equivalents of Cs 2 CO 3 (Scheme ) . The synthetic utility of this method was demonstrated by the conversion of benzo[ c ]chromen‐6‐one derivatives into pharmaceutically important terphenyls ( 27 ) in good yields by using MeI in the presence of KOH in wet DMSO at room temperature.…”
Section: Cs2co3‐mediated Benzannulation Reactionsmentioning
confidence: 99%